SMART BUILDINGS : TECHNOLOGY AND THE DESIGN OF THE BUILT ENVIRONMENT - Bakker, Ron author 632172 (London : RIBA Publishing, 2020)
How is technology shaping our built environment and changing the practice of architecture? This book explores how buildings and spaces are designed, built, used, and better understood through technology. A practical guide to technical advances including Internet of Things (IoT), 3D printing, innovative materials and robotics, Smart Buildings also outlines the opportunities for architecture including improved communication, flexibility, wellbeing, productivity and data collection. Bringing together multidisciplinary contributions and case studies from across the globe, this book provides an inspiring practical guide on how technology can inspire new architectural ideas, improving quality, comfort, health and wellbeing in the built environment.